2018
DOI: 10.1016/j.ijsu.2017.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Engagement and role of surgical trainees in global surgery: Consensus statement and recommendations from the Association of Surgeons in Training

Abstract: There is a role for surgical trainees to become involved in Global Surgery, especially in partnership with local surgeons and with appropriate ethical consideration. Trainees develop translational skills in resource poor settings. Development of appropriate pathways for recognition of global surgery experience for CCT should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…International surgeons handling the workload and local surgeons ready for private practice will result in a temporary management of hospital capacities only. NGO have surely understood this point, but the implementation was not successful everywhere [23,24]. A well-equipped hospital with low surgical expertise probably is not as effective as a low equipped hospital with well trained staff.…”
Section: Discussionmentioning
confidence: 99%
“…International surgeons handling the workload and local surgeons ready for private practice will result in a temporary management of hospital capacities only. NGO have surely understood this point, but the implementation was not successful everywhere [23,24]. A well-equipped hospital with low surgical expertise probably is not as effective as a low equipped hospital with well trained staff.…”
Section: Discussionmentioning
confidence: 99%
“…Interest among HIC trainees wanting increased exposure to global surgery is high104–107; however, several barriers limit the development of any formalised training pathway, such as logistical and time constraints or limited funding opportunities 104 107. Such formalised training could, however, prove feasible within current training models108 and may even benefit home health organisations 109. Ensuring that institutional partnerships are developed is essential to allow for bidirectional international exchanges93; however, sustainability and high ethical standards must be ensured.…”
Section: Volunteering and Charitable Supportmentioning
confidence: 99%
“…2 , 3 The complexities and ethical issues of working in LMICs were acknowledged during a consensus meeting at the Association of Surgeons in Training (ASiT) Conference in 2016 and it was suggested that offering what the local countries actually need and not what we think they need is key in global surgery. 4 As trainees' interest in Global Reconstructive Surgery (GRS) grows, so must the availability of educational resources, opportunity and guidance. This manuscript explores trainees' attitudes towards GRS and introduces the British Foundation for International Reconstructive Surgery and Training (BFIRST) Trainees Group which aims to act as a platform to promote trainees' involvement.…”
Section: Addressing An Unmet Need For Global Reconstructive Surgical mentioning
confidence: 99%
“…Even though the role of trainees in overseas projects has been debated, there is evidence that trainees' involvement can boost the success and sustainability of global surgical collaborations. 4 Arguably the establishment of educational standards, best-practice guidelines and accreditation of curricula are essential to legitimise the field of global surgery in the UK post-graduate medical education.…”
Section: Addressing An Unmet Need For Global Reconstructive Surgical mentioning
confidence: 99%